1999
DOI: 10.1007/s003390050999
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of carbon nanotubes

Abstract: A variety of outstanding experimental results on the elucidation of the elastic properties of carbon nanotubes are fast appearing. These are based mainly on the techniques of high-resolution transmission electron microscopy (HRTEM) and atomic force microscopy (AFM) to determine the Young's moduli of single-wall nanotube bundles and multi-walled nanotubes, prepared by a number of methods. These results are confirming the theoretical predictions that carbon nanotubes have high strength plus extraordinary flexibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
700
2
6

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,364 publications
(723 citation statements)
references
References 33 publications
15
700
2
6
Order By: Relevance
“…Thus, the Zn/Al complex consists of Al(CH3COO)3 acting as the amphiphilic carrier and a complex of Zn 2+ and NO 3 − ions acting as the hydrophilicity carrier; the Zn/Al complex is amphiphilic. Since Zn(NO3)2 cannot disperse SWCNT in water, and Al(CH3COO)3 gives rise to an extremely poor dispersion of SWCNT (Fig.…”
Section: The Interactions Between Zn/al Complex and Swcnt And Dispersmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the Zn/Al complex consists of Al(CH3COO)3 acting as the amphiphilic carrier and a complex of Zn 2+ and NO 3 − ions acting as the hydrophilicity carrier; the Zn/Al complex is amphiphilic. Since Zn(NO3)2 cannot disperse SWCNT in water, and Al(CH3COO)3 gives rise to an extremely poor dispersion of SWCNT (Fig.…”
Section: The Interactions Between Zn/al Complex and Swcnt And Dispersmentioning
confidence: 99%
“…Single-wall carbon nanotubes [1] (SWCNT) are known to possess outstanding physical and chemical properties such as high electrical and thermal conductivities, photo luminescence, and mechanical properties [2][3][4][5]. However, pure SWCNT form firm bundles [6], which hampers their application to various technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Since the official report of carbon nanotubes (CNTs) by Iijima in 1991 [1], they have been expected to be a promising reinforcement in composite materials processing because they remarkably show superior mechanical properties such as high Young's modulus of about 1TPa and tensile strength of about 20 GPa [2][3][4]. Recently, CNTs have been widely used as reinforcing materials for metal matrix composites (MMCs).…”
Section: Introductionmentioning
confidence: 99%
“…Since carbon nanotubes (CNTs) were discovered, great studies have been made in exploiting their properties [1,2]. Theoretical and experimental studies have shown that these materials possess both excellent mechanical properties, such as elastic moduli as high as 1 TPa and strengths from 10 to 100 times higher than the strongest steel at a fraction of the weight, excellent toughness and superior physical properties, such as thermal conductivity about twice as high as diamond and electric current-carrying capacity 1000 times higher than copper wires [3,4].…”
Section: Introductionmentioning
confidence: 99%